Nutrient intakes from solid/semisolid foods and body fat of children 12-36 months of age in Mumbai city, India - Bagle, Namrata Nitin; Udipi, Shobha Anand (Indian Journal of Child Health, 2017)
Background: Few reports are available on the association between feeding practices and body fat of young Asian Indian children. Indian children have “thin-fat” syndrome, i.e., they tend to have higher body fat at lower body mass index, placing them at risk of non-communicable diseases. Objectives: The objective of this study is to examine whether young children’s nutrient intakes are associated with body fat. Materials and Methods: Percent body fat measured by bioelectric impedance and nutrient intakes estimated from three 24-h diet recalls were studied in 1200 children, aged 12-36 months. Average intakes of macronutrients and micronutrients were calculated. Nutrient intakes were compared by quintiles of body fat. Results: Mean body fat was 20.13±2.37%, with older children having more body fat than younger children. Males had more body fat than females. Percent body fat was not only correlated with macronutrient intakes but also was positively correlated with iron, zinc intakes, and thiamine. Body fat was negatively associated with calcium, fiber, and Vitamin A intakes but was positively associated with intakes of animal protein and from milk and milk products. Children in the highest quintile of body fat had lower calcium intakes those in lower quintiles. Animal protein intakes increased from Quintile 1 to Quintile 4 of body fat. Male children aged 12-24 months in the second and third quintile had higher mean protein intakes than in the other quintiles. Female children in the highest quintile of body fat had lower mean animal protein intakes. Breastfed children aged 24-36 months old in Quintile 1 had lower protein intakes from milk and milk products than in the other four quintiles. Among non-breastfed male children, those in the fifth quintile had lowest intake of milk protein. Conclusion: Diets given to young children should be adequate in micronutrients and fiber, and there should not be too much emphasis on dairy protein only.